TUTORS AND STUDENTS ACTIVITIES IN ONLINE ARABIC LEARNING: A FREEDOM TO LEARN PERSPECTIVE - Ahmad Muradi; Jamal Syarif; Fatwiah Noor; Arif Rahman Hakim (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2021)
Arabic learning amid the Covid-19 pandemic has changed offline to online. At the same time, the government launched a merdeka belajar (freedom to learn) program. Therefore, activities that support Arabic learning are needed. This article aimed to describe the tutors' and students' activities to improve the student’s Arabic skills at UIN Antasari Banjarmasin from freedom to learn perspective. A descriptive qualitative method was used by collecting data using a survey towards students, and interviews with tutors and Language Development Unit (UPB) staff. The results of this study described tutors' and students' activities in online Arabic learning. Tutors' activities are described by the personality of tutors, teaching materials, media, methods, and learning motivation. The students' activities are described by the process of online Arabic learning and the efforts made to improve their Arabic skills. Based on tutors' and students' activities, it was found that tutors and students applied a good learning culture through activities that support the mastery of Arabic in listening, speaking, reading, and writing.